Morphometric relationships of the siphon clam Panopea globosa (Bivalvia: Hiatellidae) in the southeasternmost of the Gulf of California, Mexico - Góngora-Gómez, Andrés Martín; Sotelo-Gonzalez, Maria Isabel; Santamaría-Miranda, Apolinar; García-Ulloa, Manuel (Revista de Biología Marina y Oceanografía, 2019)
The morphometric relationships of the siphon clam Panopea globosa from Sinaloa, Mexico, were analyzed from February 2014 to April 2015. A total of 370 specimens were collected, measured (shell length, width, and height) and weighed (body weight, tissue weight, and shell weight). The coefficient of determination indicated variation in the fitting of morphometric variables among measured traits. The type of relative growth for all morphometric relationships was negative allometry. This is the first report on morphometric relationships of P. globosa from Sinaloa, Mexico.